Effect of chitosan as a coupling agent and types of stabiliser of zirconia filler on nanocomposite hardness - Putri, Tansza Permata Setiana; Manurung, Rosida; Usri, Kosterman; Purwasasmita, Bambang Sunendar (Padjadjaran Journal of Dentistry, 2018)
Introduction: Nanocomposite has been developed as a dental restoration. Nano-scale filler can result in high mechanical properties and good esthetic. Nanofiller materials such as partially stabilised zirconia (PSZ) has been recommended for dental use. This form of zirconia can be stabilised by the addition of several different oxides such as magnesia and calcia. Chitosan as a coupling agent was able to increase the nanocomposite’s mechanical properties. The purpose of this research was to evaluate the nanocomposite’s hardness value with and without the addition of chitosan as a coupling agent as well as a different stabiliser of zirconia filler. Methods: Procedures of this research consisted of several stages which were the fabrication of nanocomposite and mechanical properties measurement using the Vicker’s hardness testing. Results: The nanocomposite’s hardness value (kg/mm2) with zirconia filler stabilised by MgO without the addition of chitosan was as much as 5.09 and with the addition of chitosan was 7.51; the nanocomposite ’s hardness number with zirconia filler stabilised by  CaO without the addition of chitosan was 8.16 and with the addition of chitosan was 13.13.  The results were then analysed statistically using the Analysis of Variance (ANOVA) test and showed a significant difference between all of those data groups. Conclusion: The addition of chitosan as well as different stabiliser (MgO and CaO) of Zirconia filler had affected the nanocomposite ’s hardness value.